Some New Directions for Research on the Biology of Aging - MARTIN, GEORGE M. (Annals of the New York Academy of Sciences, 2000)
: A highly selective, eclectic, and personal view of new directions and new opportunities for research on the biology of aging is briefly outlined. Some concern is raised regarding the present emphasis on the use of centenarians for the definition of genetic loci responsible for unusually robust retention of structure and function. More progress is likely to be made were we to focus on the genetic basis for “elite” aging in middle‐aged subjects examined for very specific phenotypes, as these are likely to be far less polygenic. Descriptive gerontology is entering a renaissance, given such new clinical tools as functional MRI and basic science tools such as functional genomics and proteomics. Advances in genomics should expedite answers to such questions as why some avian species have exceptionally long lifespans despite unusual loads of oxidative stress. One hopes to see renewed mechanistic studies, using such tools, at the systems levels. New methodologies are permitting the evaluation of stochastic alterations in gene structure and function in postreplicative cells. The exciting work on molecular misreading should prompt us to reexplore the Orgel hypothesis as it applies to such cell types. Epigenetic shifts in gene expression that occur in association with sexual maturation and the cessation of growth may have deleterious consequences late in the life course. It will therefore be important for gerontologists to investigate the molecular biology of pubescence. Finally, our community should investigate the impact of environmental “gerontogens,” agents that accelerate specific processes of aging and specific senescent phenotypes.